2014
DOI: 10.1159/000367713
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Proliferation Assessment by Ki-67 Expression in Neuroendocrine Neoplasms: Eyeballing or Image Analysis?

Abstract: Background: The latest WHO classification for neuroendocrine neoplasms (NEN) of the gastrointestinal tract defines grade according to Ki-67 and mitotic indices. Some have questioned the reproducibility and thus the reliability of Ki-67 assessment. We therefore investigated the accuracy of this proliferation marker in NEN. Methods: The Ki-67 index of tumor specimens of NEN (n = 73) was assessed by two pathologists as in routine practice with eyeballing and twice by image analysis using ImageJ freeware at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Here, between the tumor entities, a similar constellation was found as in both manual counting methods. The data are in accordance with many other studies comparing automated digital image analysis with the manual methods, but in some investigations also higher or equal limits were observed [31, 33, 3638]. The discrepancies between published results may result from differences in the programs used for digital image analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Here, between the tumor entities, a similar constellation was found as in both manual counting methods. The data are in accordance with many other studies comparing automated digital image analysis with the manual methods, but in some investigations also higher or equal limits were observed [31, 33, 3638]. The discrepancies between published results may result from differences in the programs used for digital image analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Similar observation were made in NEN: results of eyeballed estimation differed from results of counting [20,21,25] and were irreproducible [25], but some investigators showed that estimation was not as bad [27,28]. Pathologists in general overestimate the Ki67 LI during eye-balled estimation in comparison to counting technique [25,27].…”
Section: Toward Optimal Methods Of Ki67 LI Assessmentsupporting
confidence: 64%
“…Analytical validity is a sine qua non condition for any tumour biomarker which is intended to be used in clinical practice and to influence management of the patients [18]. Selected aspects of analytical validity of Ki67 LI in NEN were previously studied [19,20,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has become clear that tumor grade based on Ki67 proliferative index is a better measure of tumor behavior than mitotic count. (2-4) Thus, accurate assessment of Ki67 proliferative index is essential for determination of tumor grade. This information, in turn, is essential for accurate prognostication and optimal patient management.…”
Section: Introductionmentioning
confidence: 99%